Simultaneous Spectrophotometric Estimation of Methotrexate and All-trans Retinoic Acid in Mixture - K. Tekade, Rakesh; Dutta, Tathagata; Jain, Neha; Gajbhiye, V.; K. Jain, Narendra (Asian Journal of Chemistry, 2010)
A novel, simple, accurate and precise UV spectrophotometric method has been developed for the simultaneous estimation of methotrexate and all-trans retinoic acid in mixture. Distinct solubility characteristics of both the drugs required the development of common solvent, which was found to be a combination containing 1.5 % v/v Tween-20 and 5.0 % methanol in PBS; pH 7.4 (PBST20Met). Based on interaction studies, both the drugs were found to be imposing no effect on the absorption maxima of each other. In the proposed method, the signals were measured at 258 and 340 nm, respectively corresponding to the absorbance maxima of methotrexate and all-trans retinoic acid (ATRA). Both the drug obeys the Lambert-Beer's law in the concentration range of 2-12 μg/mL. Results were authenticated statistically as well as by recovery studies. The method has the advantage of high sensitivity, lower limit of detection and could find a niche application in on-going research for the development of methotrexate and all-trans retinoic acid based chemotherapeutic combination for the treatment of leukemia.